UI/UX Analysis of myplpkkndik.fkip.ums.ac.id using the Heuristic Evaluation Method - Ahmad Farid Al Azhar; Arif Setiawan (Universitas Muhammadiyah Surakarta, 2025)
Myplpkkndik.fkip.ums.ac.id is one of the official websites at Universitas Muhammadiyah Surakarta, designed to facilitate students in managing their PLP (Praktik Lapangan Persekolahan) and KKN (Kuliah Kerja Nyata) activities. However, despite the platform's operation, several usability issues and user complaints persist regarding User Experience (UX) and User Interface (UI), including unattractive web design, inadequate accessibility, confusing navigation and layout, and the absence of a help menu to assist users. This study aims to analyze these issues and provide recommendations to enhance usability and user satisfaction. The research employs the heuristic evaluation method, which utilizes ten well-established principles to assess design effectiveness. Data collection was conducted using a Google Forms questionnaire, with a sample size of 92 fifth-semester students from the Faculty of Teacher Training and Education (FKIP) at Universitas Muhammadiyah Surakarta. The recapitulated results indicate that while some identified issues do not critically impact users, classified as minor problems, specific usability concerns were found on the website, particularly in: Visibility of system status (H1), User control and freedom (H3), and Help and documentation (H10).